Systemic Hemodynamic Changes after Maximally Allowable Liver Resection in Rats - P. A. Ermolaev; T. P. Kramykh; L. O. Barskaya (Общая реаниматология, 2015)
Objective: to experimentally reveal possible systemic hemodynamic changes after maximally allowable liver resection, by determining the time of their formation in the early postoperative period. Materials and methods. The experiments on 22 outbred male albino rats recorded an electrocardiogram, left carotid blood pressure by a direct method, an integral rheogram and its first derivative by the tetrapolar rheographic procedure developed by Sh. I. Ismailov et al. and modified by V. V. Karpitsky et al. 1, 3, 6, and 12 hours and 1, 3, and 7 days after maximally allowable liver resection. Stroke volume, mean blood pressure, cardiac output, and specific peripheral vascular resistance (SPVR) were calculated. Blood loss was estimated by the gravimetric method. The significance of differences was defined by Friedman ANOVA. Results. At postoperative hour 1, the low cardiac output syndrome the basis for which is a considerable reduction in stroke volume developed and persisted during the first 24 hours; an additional contribution was made by moderate bradycardia observed within the first 24 hours. On day 3 postsurgery, the hemodynamic parameters were similar to those at baseline. By 7 day of an observation, cardiac depression changed into moderate myocardial hyperdynamia in the presence of moderate tachycardia and a moderate decrease in SPVR. Conclusion. The critical time found by the authors for the minimum cardiac output was an hour after surgery. The distinctive features of low cardiac output syndrome after maximally allowable liver resection are its reversible pattern and reflectory bradycardia on postoperative day 1. By day 7, cardiac depression changed into moderate myocardial hyperdynamia due to a tendency towards tachycardia.